Distribution and photodegradation of typical nonsteroidal anti-inflammatory drugs in an ice-water system: Simulation of surface waters with an ice cover. (20th May 2023) - Wang, Yakun; Song, Ziwei; Zhang, Liwen; Dong, Deming; Li, Zhuojuan; Sun, Heyang; Wang, Liting; Guo, Zhiyong
Abstract: In surface waters at middle and high latitudes during winter, the coexistence of ice and water is a natural phenomenon. Nonsteroidal anti-inflammatory drugs (NSAIDs) as emerging contaminants have been found frequently in aquatic environments, including waters that are seasonally covered in ice. However, little is available for the environmental behaviors and fate of NSAIDs in ice, particularly in the system where ice and water coexist. In this study, the distribution and photodegradation of model NSAIDs naproxen (NPX), diclofenac (DCF), and acetaminophen (APAP) in an ice-water system were investigated. The findings demonstrated a 66.7%, 60.5%, and 66.7% increase in the ice-water distribution coefficient K iw of NPX, DCF, and APAP with initial concentrations of 10 ng L −1 relative to 500 ng L −1 . The K iw values were in decreased order of DCF, NPX, and APAP. The photodegradation rate constants of NPX, DCF, and APAP in ice increased by 27.0%, 35.6%, and 56.6% relative to those in water. With the increase in freezing time, the contribution ratios of distribution to the mass loss of NPX, DCF, and APAP increased by 19.9%, 21.1%, and 16.1%, respectively. The ratios of photodegradation to the mass loss of NPX, DCF, and APAP decreased by 5.0%, 5.7%, and 0.9%, respectively. An ice cover as the predominant factor could affect the distribution and photodegradation of drugs in the surface water. This study can close a knowledge gap regarding the transport and transformation of NSAIDs in the ice-water system and provide fresh insights into the behaviors and fate of emerging contaminants in seasonally ice-covered waters. Graphical abstract: Image 1 Highlights: Solute-rich boundary layer was vital in affecting the distribution of NSAIDs. Compared with C 0 at 500 ng L −1, K iw of DCF increased by 60.5% at 10 ng L −1 . Order of photodegradation rate constants in systems was ice > water > ice-water. Distribution and photodegradation of three NSAIDs were related to their structure. Fate of NSAIDs in the ice-water system was co-regulated by the two behaviors.